2008
DOI: 10.1057/pb.2008.4
|View full text |Cite
|
Sign up to set email alerts
|

Soft power: Power of attraction or confusion?

Abstract: Despite its popularity soft power remains power of confusion. The paper examines the concept, with a special focus on the nature and sources of soft power. Nye"s notion of soft power is largely ethnocentric and based on the assumption that there is a link between attractiveness and the ability to influence others in international relations. This poses two problems: Firstly, a country has many different actors. Some of them like the attraction and others don"t. Whether the attraction will lead to the ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 19 publications
0
87
0
6
Order By: Relevance
“…Indeed, despite its growing significance, many have strongly criticized Nye's work. 48 Through these authors' attempts to unpick, understand and extend soft power theoretically, Nye's original concept has been, and, more importantly, continues to be, questioned on four specific levels: first, many have raised concerns over what soft power actually is, and, more specifically, whether it is merely another buzzword for conceptualizing that of nation branding and/or place marketing; 49 second, many have suggested that Nye fails to deliver a clear description of how one actually acquires 'soft power' or forms of attraction, leading to the concept becoming highly confusing and problematic to work with; 50 third, due to Nye's reliance on discussions of the West, many equate soft power as being either too structural or Western-centric; 51 and finally, some have argued that greater academic attention is needed in identifying and highlighting the potential pitfalls for any state that attempts to acquire soft power forms. 52 In responding to the first criticism above, Nye himself -along with others -has been quick to remind us that soft power should not merely be considered another term for place marketing/nation branding.…”
mentioning
confidence: 99%
“…Indeed, despite its growing significance, many have strongly criticized Nye's work. 48 Through these authors' attempts to unpick, understand and extend soft power theoretically, Nye's original concept has been, and, more importantly, continues to be, questioned on four specific levels: first, many have raised concerns over what soft power actually is, and, more specifically, whether it is merely another buzzword for conceptualizing that of nation branding and/or place marketing; 49 second, many have suggested that Nye fails to deliver a clear description of how one actually acquires 'soft power' or forms of attraction, leading to the concept becoming highly confusing and problematic to work with; 50 third, due to Nye's reliance on discussions of the West, many equate soft power as being either too structural or Western-centric; 51 and finally, some have argued that greater academic attention is needed in identifying and highlighting the potential pitfalls for any state that attempts to acquire soft power forms. 52 In responding to the first criticism above, Nye himself -along with others -has been quick to remind us that soft power should not merely be considered another term for place marketing/nation branding.…”
mentioning
confidence: 99%
“…When the main ethnic group in a nation holds a negative view of another nation, soft power tactics are unsuccessful even when the nations are ethnically linked. In relation to the importance of reputation, Fan (2008) explains that soft power effectiveness is determined by the perception of the population in the target country and therefore, soft power policies and initiatives must be tailored to ethnic, religious and cultural preferences of targeted populations.…”
Section: Soft Power Overviewmentioning
confidence: 99%
“…These are: political brand, economic brand and cultural brand. [21] Any country of a larger size and longevity of existence usually has an existing brand. This is the result of people having heard about them, and possessing certain images, associations and opinions.…”
Section: Nation Branding and International Reputationmentioning
confidence: 99%
“…"The relevance and ultimate effectiveness of soft power depends on the perception and response of its target audience". [47] There has been a great deal of discussion in Russia concerning soft power and public diplomacy, how these concepts currently relate and how to develop the potential further. One of the debates has been to look at the United States and see if there is anything that can be learned and applied for Russia.…”
Section: Soft Powermentioning
confidence: 99%
See 1 more Smart Citation